Serum interleukin-6, procalcitonin, and C-reactive protein at hospital admission can identify patients at low risk for severe COVID-19 progression - Zobel, Christian Matthias; Wenzel, Werner; Krüger, Jan Philipp; Baumgarten, Ulrich; Wagelöhner, Tobias; Neumann, Nino; Foroutan, Behruz; Müller, Rico; Müller, Annette; Rauschning, Dominic; Schüßler, Meike; Scheit, Lorenz; et al. (Frontiers in Microbiology, 2023)
Background: COVID-19 can show a variable course, from asymptomatic infections to acute respiratory failure and death. For efficient allocation of resources, patients should be stratified according to their risk for a severe course as early as possible. Methods: 135 hospitalized patients with COVID-19 pneumonia at four German hospitals were prospectively included in this observational study. A standardized clinical laboratory profile was taken at hospital admission and a panel of serum markers with possible roles in the COVID-associated cytokine storm were also determined. 112 patients could be evaluated. The primary endpoint of ventilator requirement or death within 30 days of symptom onset was met by 13 patients. Results: Serum elevations of interleukin-6 (IL-6), procalcitonin (PCT), and C-reactive protein (CRP) at hospital admission were each highly significantly (p < 0.001) associated with ventilator requirement/death within 30 days of symptom onset. With a sensitivity of 92 % and a specificity of 65-67 %, IL-6 ≥ 52.8 pg/ml, PCT ≥ 0.11 ng/ml, and CRP ≥ 71.1 mg/l were predictive of a severe course of COVID-19. Positive likelihood ratios were between 2.6-2.8 and negative likelihood ratios were between 0.11-0.13 for these three markers. Conclusion: Negative likelihood ratios indicate that IL-6, PCT, and CRP at hospital admission can be used for identifying patients at low risk for severe COVID-19 progression.